Symantic Literatur Review Riset Etnomatematika Menggunakan Bibliometrix R Studio Bibblioshiny : DOI 10.58569/jies.v3i1.1052 - Febriyanti , Chatarina; Handayani, Shinta Dwi; Irawan, Ari (Pascasarjana Universitas Islam Jakarta, 2024)
The aim of this literature review is to analyze the trend of development of articles published by Scopus with a time span of 40 years from 1984-2024, as a material for study to forecast research that will be carried out by the next researcher. The method of writing this article uses a semantic literature review with the tools used is bibliometric analysis with R Studio biblioshiny. The stages of analysis activities by collecting articles through Scopus API Key with the keyword Ethnomathmematics found as many as 618 documents from journals, books, book chapters and others. Furthermore, an analysis of the results of data visualization from biblioshiny is carried out. The results of the study found that Indonesia,both authors and institutions, wrote many articles related to ethnomathematics. New themes were found that are relevant for ethnomathematics research that are linked to cryptography, curriculum, augmented reality and others, so that prospective researchers can link ethnomathematics with interdisciplinary studies